Python for data science : a hands-on introduction - Vasiliev, Yuli (No Starch Press, 2022)
"Shows programmers the best ways to leverage Python for data-driven applications. Loaded with practical examples, the book provides a wide-ranging tour of Python's abilities to obtain, transform, and analyze data"--